Evaluation of Applications Made To a Migrant Health Center in Elazığ - Oğuzöncül, Ayşe Ferdane; Kara, Kevser Tuncer (Göç İdaresi Başkanlığı, 2021)
Aim: In this study, it was aimed to determine the demographic information of the immigrants who applied to the immigrant health center, the reasons for their application and the issues that should be given importance in the improvement of immigrant health. Materials and Methods: This research is descriptive and cross-sectional. The applications made to the immigrant health center within a year were evaluated. Statistical evaluations were made in SPSS 22.0 software, t and chi-square tests were used. Results: During the period included in our study, 13,464 (74%) outpatient clinic, 4048 (22.2%) immunization and 692 (3.8%) family planning applications were recorded, 18,204 in total. The number of applications to the migrant health center per person was 1.28/year. It was observed that women applied to polyclinics more than men (p<0.001). The most common cause of outpatient admission was upper respiratory tract infection. Conclusion: As a result, it is observed that migrant women apply to immigrant health centers more than men. When the outpatient applications are examined in detail, the applications due to infectious diseases are the most frequent. It is thought that immigrants need training on Mother-Child Health and Family Planning (MCH/FP) and hygiene.

Amaç: Bu çalışmada, göçmen sağlığı merkezine başvuran göçmenlerin demografik bilgilerinin, başvuru nedenlerinin ve göçmen sağlığının geliştirilmesinde önem verilmesi gereken konuların tespiti amaçlanmıştır. Gereç ve Yöntemler: Araştırma tanımlayıcı, kesitseldir. Çalışmamızda göçmen sağlığı merkezine bir yılda yapılan başvurular değerlendirilmiştir. İstatistiksel değerlendirmeler SPSS 22.0 programında yapılmış, t ve ki-kare testleri kullanılmıştır. Bulgular: Çalışmamız kapsamına alınan sürede toplam 18.204 olmak üzere; 13.464 (%74) poliklinik, 4048 (%22,2) bağışıklama, 692 (%3,8) aile planlaması başvurusu kaydedilmiştir. Kişi başına düşen göçmen sağlığı merkezine başvuru sayısı;1,28/yıldır. Kadınların erkeklere göre daha fazla polikliniğe başvurduğu görülmüştür (p<0,001). En sık poliklinik başvurusu nedeni üst solunum yolu enfeksiyonudur. Sonuç: Sonuç olarak, göçmen kadınların erkeklere oranla daha fazla göçmen sağlığı merkezine başvurduğu görülmüştür. Poliklinik başvuruları ayrıntılı incelendiğinde enfeksiyon hastalıkları nedenli başvurular en sıktır. Kronik hastalık ve AP nedenli başvuruların az sayıda oluşu dikkat çekmiştir. Göçmenlerin Anne-Çocuk Sağlığı ve Aile Planlaması (AÇSAP) ve hijyen konularında eğitim gereksinimi olduğu düşünülmektedir.
Elazığ’da Bir Göçmen Sağlığı Merkezine Yapılan Başvuruların Değerlendirilmesi